Antidiarrheal Activity of n-Hexane Fraction Seeds of Leucaenae leucocephala (Lam) de Wit on Rat - Husein, Saddam; Nainggolan, Marline; Y, Yuandan (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: To evaluate the antidiarrheal activity of the n-hexane fraction of L. leucocephala (Lam) de Wit seeds induced by castor oil and intestinal motility methods for rats. Method: L.leucochepala seeds simplicia powder extracted by maceration with 80% ethanol. Ethanol extract was fractionated with n-hexane solvent. Investigating of antidiarrheal activity of L.leucocephala fraction by induction of castor oil and intestinal motility methods. Result: The n-hexane L.leucocephala fraction reduced diarrhea based on observations of the onset of diarrhea, frequency, consistency, weight of stool and duration of diarrhea compared with negative controls. The n-hexane L.leucocephala fraction showed antidiarrheal activity at doses of 200 and 400 mg/kg bw (P <0.05) but differed significantly from loperamide (P <0.05). In the intestinal motility method of the n-hexane fraction doses of 200 and 400 mg/kg bw the activity in inhibiting intestinal motility was significantly different from 0.5% CMC Na (P <0.05). Conclusion: Then-hexane fraction of L. leucocephala seeds based on antidiarrheal activity testing has the ability to reduce diarrhea.